Challenges faced by caregivers raising children left by deported migrant parents in Johannesburg, South Africa - Patiance Sekesai Zhou; Frans Koketso Matlakala (Cogent Social Sciences, 2024)
This paper was aimed at exploring challenges faced by caregivers raising children left by deported migrant parents in Johannesburg, South Africa. Researchers employed a qualitative research approach and adopted an exploratory case study design. The sample consists of 12 caregivers, selected through purposeful sampling, engaging in semi-structured interviews. Thematic analysis was used to derive key themes from the caregivers’ narratives, allowing for a comprehensive exploration of their experiences and the challenges faced in informal caregiving. The findings reveal a pervasive informal caregiving landscape, where caregivers assume parental responsibilities without formal government involvement. Caregivers face challenges such as financial constraints, limited access to statutory social services, access to healthcare barriers, feelings of stress and helplessness, and difficulties in family tracing and reunification. The lack of documentation for migrant children exacerbates these challenges, hindering their access to essential services. The study concludes that the informal nature of caregiving arrangements for children of deported migrants in South Africa poses significant risks to their well-being. The study recommends the inclusion of formalising alternative care arrangements, improving access to statutory social services, addressing access to healthcare barriers, providing support for caregivers’ mental health and financial well-being, advocating for documentation, and strengthening family tracing and reunification processes.